Analisis Manajemen Sumber Daya Manusia untuk Meningkatkan Kinerja PT Hung A Indonesia: Damas Elvianto, Sindi Framita, Syahwatul Khalda*, Risma Rahayu, Krisdayanti, Suryanti - Damas Elvianto; Sindi Framita; Syahwatul Khalda; Risma Rahayu; Suryanti (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
Human resources play an important role in every business because having sufficient human resources makes it easier for a company to achieve its goals. This target can be achieved if you have a good level of human resources to show the level of effectiveness and efficiency of each employee. Good human resource management allows companies to retain good employees and significantly improve productivity. The type of research used was descriptive qualitative research. The data collection methods used in this study were observation and interviews. The results of this study are related to human resource management by PT Hung A Indonesia, namely by developing organizational culture, providing incentives, establishing good relationships between employees and suppliers, paying attention to the leadership style used, orientation, training and development, reward system, recruitment and selection, as well as appointment and placement of employees.